Efeitos cardiovasculares e renais da injeção intra-arterial de contraste radiológico iônico em cães com restrição hídrica - Lima Verderese, Marisa Aparecida [UNESP]; Galvão Vianna, Pedro Thadeu [UNESP]; Machado Castiglia, Yara Marcondes [UNESP]; Antonio Vane, Luiz [UNESP] (My University, 2005)
BACKGROUND AND OBJECTIVES: This study aimed at evaluating acute radiological contrast effects in fluid restriction situations, observing renal and cardiovascular effects after intra-arterial injection of high osmolarity radiological contrast. METHODS: Participated in this study 16 dogs anesthetized with sodium thiopental (15mg.kg -1) and fentanyl (0.03 mL.kg -1), followed by continuous infusion of 40 μg.kg -1.min -1 (sodium thiopental) and 0.1 μg.kg -1.min -1 (fentanyl). Hydration was achieved with 5% glucose solution (0.03 mL.kg -1.min -1) and ventilation was mechanically controlled with compressed air. The following attributes were evaluated: heart rate (HR); mean blood pressure (MBP); inferior vena cava pressure (IVP); cardiac output (CO); hematocrit (Ht); effective renal plasma flow (ERPF); renal blood flow (RBF); glomerular filtration rate (GFR); filtration fraction; renal vascular resistance (RVR), urinary volume (UV); plasma and urinary osmolarity; osmolar clearance; free water clearance; sodium and potassium clearance; plasma sodium and potassium; sodium and potassium urinary fractional excretion and rectal temperature. These attributes were evaluated in four moments: 30 (M1), 60 (M2), 90 (M3) and 120 (M4) minutes after sodium para-aminohipurate and creatinine administration (beginning of experiment). In moment 2, G1 received intra-arterial 0.9% saline (1.24 mL.kg -1) and G2 received intra-arterial radiological contrast (1.4 mL.kg -1). RESULTS: Group G1 has presented increased HR, ERPF, RBF, plasma osmolarity, sodium clearance and sodium urinary excretion, in addition to decreased urinary osmolarity, plasma sodium, potassium clearance and rectal temperature. Group G2 has presented increased HR, RVR, UV, osmolar clearance, sodium clearance and sodium urinary and fractional excretion; there has also been decrease in hematocrit, glomerular filtration rate, filtration fraction, urinary osmolarity, free water clearance, urinary sodium and potassium, plasma potassium and rectal temperature. CONCLUSIONS: This study has concluded that intra-arterial radiological contrast has promoted a two-phase effect on renal function. Initially it has promoted increased diuresis and sodium excretion but then the hemodynamic conditions impaired, and consequently renal function impaired, with increased renal vascular resistance and decreased glomerular filtration rate. © Sociedade Brasileira de Anestesiologia, 2005.
Cardiovascular and renal effects of intra-arterial injection of ionic radiological contrast in dogs under fluid restriction
Keywords: Animals: dogs; Cardiovascular system; Contrast media; Hemodynamic; Kidney: function